2014
DOI: 10.9790/0661-1625113116
|View full text |Cite
|
Sign up to set email alerts
|

Network Layer Attacks and Their Countermeasures in Manet: A Review

Abstract: Mobile ad hoc network(MANET) is a collection of mobile nodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Certainly the complexity of addressing schemes is raised. For the attack of Packet Drop there are a two collapsed approach, to recognize and after that to confine such nodes is presented which turns into the piece of the network to bring about packets dropping assaults [61]. To protect against Impersonation Attack a multifaceted validation network is suggested that amplifies the cryptographic connection, restricting a substance to a physical node gadget.…”
Section: Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly the complexity of addressing schemes is raised. For the attack of Packet Drop there are a two collapsed approach, to recognize and after that to confine such nodes is presented which turns into the piece of the network to bring about packets dropping assaults [61]. To protect against Impersonation Attack a multifaceted validation network is suggested that amplifies the cryptographic connection, restricting a substance to a physical node gadget.…”
Section: Attackmentioning
confidence: 99%
“…This arrangement keeps the replay assault by looking at the present time and time stamp contained in the got message. On the off chance that the time stamp is too a long way from the present time, the message is judged to be suspicious and is rejected [61].…”
Section: Man-in-the-middle Attacksmentioning
confidence: 99%